"An Ocean of Noise": H.E. Reilley and the Making of a Legitimate Social Problem, 1911-45 - Rudy, Jarrett; Kenny, Nicolas; Fahrni, Magda (Journal of Canadian Studies / Revue d'études canadiennes, 2017)
Keywords: Physique; Université McGill

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Cyclist Injury Risk and Pollution Exposure at Urban Signalized Intersections - Strauss, Jillian (Université McGill, 2012)
Keywords: Cyclisme; Pollution

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

The Evolution of Montreal's Precipitation: Climate - Leduc, Richard (Université McGill, 1977)
Keywords: Climat

A Study of the Relationship between Ecological and Non-Ecological Factors in the Development of Certain Natural Areas of Montreal - Richardson, Nigel H. (Université McGill, 1954)
Keywords: Notre-Dame-de-Grâce; Quartiers; Rosemont; Snowdon

The Natural Areas of the Montreal Metropolitan Community with Special Reference to the Central Area - Zatuka, Leo (Université McGill, 1948)
Keywords: Parcs

Community Response to Environmental Change: A Case Study of Montreal's West Island 1981-1991 - Adams, Jennifer (Université McGill, 1992)
Keywords: Quartiers; West Island

Movement, Morphology and Circulation of Montreal Summer Storms - Shaw, Roderick (Université McGill, 1970)
Keywords: Climat

Une étude bioclimatique de la ville de Montréal - Lafleur, Daniel (Université McGill, 1972)
Keywords: Climat

Dynamics of Heavy Warm Season Precipitation Events in Montréal - Dookhie, Giselle C. (Université McGill, 2011)
Keywords: Climat

A Synoptic Climatology of Ground-Level Ozone for Montreal, Quebec - Stephens, Kate (Université McGill, 1995)
Keywords: Climat

A Synoptic Climatology of Montreal Precipitation - Fischer, Alexander P. (Université McGill, 1998)
Keywords: Climat

Climate and Architecture: With Special Reference to Montreal and Surroundings - Aronin, Jeffrey Ellis (Université McGill, 1951)
Keywords: Climat

Freezing Rain in the Montreal Area - Leech, Margaret E. (Université McGill, 1978)
Keywords: Climat

The Petrology of a Part of Westmount Mountain near Summit Circle, Montreal - Malouf, Stanley Edward (Université McGill, 1936)
Keywords: Géographie physique

Planetary and Synoptic-Scale Analysis of Freezing Rain Events in Montreal, Quebec - Ressler, Gina (Université McGill, 2010)
Keywords: Climat

Stewardship as Partnership: A Comparative Study of Positive Human-Environment Relationships in East Cree and Suburban Montreal Communities - Forrest, Margaret Anne (Université McGill, 2006)
Keywords: Banlieue; Parcs; Pointe-Claire

A Community of Believers and Healers: Learning from the functional characteristics of Hôtel Dieu - McDonald, Marie-Pierre (Université McGill, 2014)
Keywords: Communautés religieuses; Hôpitaux; Hôtel-Dieu